HEALTHCARE PROVIDER DURNOUT AND STRATEGIES FOR PREVENTION - Deya Ahmed Alshawmari; Alaithan , Hassan Radhi A; Ayman Abdullah Alhumaid; Mansour Ali M Al Jumiaan; Alramadan, Haider Naim Mohammed; Sajjad Redha Mohammed Alturfi; Almenyan, Zahra Ali Qassim; Ali Fadel Aleissa; Rasha Ali Alyafei; Zahra Ali Alsuwidany; Hawra Abbas Alqallaf; Zahra Abdullah Al-Alwan; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Healthcare provider burnout is a pervasive issue that impacts the well-being of individuals working in the healthcare industry and can have significant implications for patient care and outcomes. This review article aims to explore the causes and consequences of healthcare provider burnout, as well as evidence-based strategies for prevention and mitigation. The article synthesizes current research findings on burnout among healthcare professionals, including physicians, nurses, and other staff members. Factors contributing to burnout, such as high workload, emotional exhaustion, and lack of resources, will be examined. Additionally, the impact of burnout on job satisfaction, quality of care, and patient safety will be discussed. Furthermore, this review will highlight various interventions and strategies that have been proposed or implemented to address healthcare provider burnout. These may include organizational interventions, such as improved work environment and support systems, as well as individual-level strategies like mindfulness training and self-care practices. The effectiveness of these interventions in reducing burnout and promoting well-being among healthcare providers will be evaluated. Overall, this review aims to provide a comprehensive overview of healthcare provider burnout and offer insights into potential preventive measures that can be adopted at both the individual and organizational levels. By understanding the complex nature of burnout and implementing targeted strategies, healthcare institutions can create a healthier and more sustainable work environment for their staff, ultimately improving patient outcomes and overall quality of care.